Predicting the ageing time of thin film sacrificial copper strip sensors over a wide range of DBDS concentrations - Ahmad Khiar, Mohd Shahril; Zulkefli, Nur Izyan Husnina; Ab Ghani, Sharin; Sutan Chairul, Imran; Rahim, Nor Hidayah; Ahmad, Asimi Ana (Semarak Ilmu Publishing, 2023)
Catastrophic transformer failures are often attributed to corrosive sulphur-related faults. However, the existing challenge lies in the absence of practical, real-time monitoring techniques for sulphur corrosion, especially on-site. Previous studies have proposed the use of thin film sacrificial copper strip sensors as a promising solution to address this issue. Yet, their effectiveness in detecting corrosive by-products resulting from varying concentrations of DBDS breakdown remains unexplored. To bridge this knowledge gap, this study introduces an alternative technique that utilizes MATLAB software for linear interpolation and extrapolation. The findings demonstrate the capability of this technique to predict the ageing time of thin film sacrificial copper strip sensors when exposed to corrosive by-products derived from DBDS breakdown across a broad concentration range. This research aims to provide a valuable contribution towards enabling effective monitoring of sulphur corrosion and enhancing transformer maintenance practices.